Comparative Analysis of the Efficiency of Reverse Osmosis and Hydroxyapatite for Fluoride Removal in Water: A Case of AUWSA - Daniel, Peter; Macha, Innocent J. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Water treatment technology selection depends on contaminant type and budget. Fluoride removal from water is particularly challenging, requiring non-conventional treatment technologies (Radwan, 2023). Several regions in Tanzania, including Arusha City, are affected by fluoride contamination. With a population of 617,631 (Census, 2022), only 117,763 people currently have access to clean water supplied by AUWSA. This study aimed to compare the efficiency of Reverse Osmosis (RO) and Hydroxyapatite (HAP) in fluoride removal as a strategy to address water quality and supply challenges. Experiments were conducted using 6 m³ of raw water with fluoride concentrations ranging from 5.1 mg/L to 6.83 mg/L, sourced from boreholes. The HAP pilot plant was tested at 30-minute intervals from 8:00 AM daily for 21 days, while the RO system was tested with the same water volume at 5-minute intervals over the same period. Laboratory analyses of raw and treated water revealed that HAP had a lower fluoride removal efficiency of 91.51% to 93.41%, compared to RO, which achieved 96.05% to 97.66% removal efficiency. It was also revealed that RO loses about 30% of water during treatment, while HAp doesn’t lose any. Moreover, HAp uses locally available biogenic materials for treatment, enhancing sustainability. The findings suggest that the HAP treatment system is a practical and sustainable solution, offering effective fluoride removal while remaining affordable and energy-efficient, making it a viable choice for communities in need of clean and safe drinking water. This research addressed the problem of excess fluoride concentration in water and availability and access of clean water. Further research is recommended to evaluate the environmental implications of waste disposal following HAP media regeneration and the management of reject water from the RO filtration process. This assessment should focus on potential ecological risks, long-term sustainability, and the development of environmentally friendly disposal or reuse strategies.